Effect of supplementing two types of food flavor in diet on production of Japanese quail - Hamad, Rashad F.; Al–Shadeedi, Shahrazad M. B. (Journal of Kerbala for Agricultural Sciences, 2018)
The aim of this novel study which is the first study in Egg production technology through the use of different concentrations of two types of food flavors used in the feed, the first is vanilla and the second one is the orange flavor, as well as improve some of the eggs produced of Japanese quail birds. Practical part of research was conducted at the college of Agriculture at Abu Ghraib / University of Baghdad for the period from 23/9/2016 until 30/12/2016. The 30-day-old Japanese quail were reared in cages .Two types of food flavors( the vanilla flavor and orange flavor) were used (powder form), Spanish made were purchased from commercial markets located in the area of Shorja / Baghdad. The animals were divided into five groups with two replicates for each group: First: Control group (without any addition to feed), Second : 1% vanilla flavor was added to feed. Third: 0.5% vanilla flavor was added to feed . Fourth: 1% orange flavor was added to feed. Fifth: 0.5% orange flavor was added to feed. The results of the statistical analysis of the production characteristics showed significant differences (P <0.01) which showed that best enhancement was appeared in the second and fifth treatment groups followed by the third and fourth treatment groups. The first treatment showed the lowest characteristic values in the percentage of egg production average of eggs weight, accumulative egg production, produced eggs weight and the food conversion ratio (FCR) during the last three periods of the study. In conclusion, we suggest the possibility of adding 0.5% or 1% of vanilla flavor and orange flavor respectively of this commercial food flavorings to the diet of the birds to improve productive characteristics of Japanese quail.